Platon i Arystoteles – bibliofile - Warda, Elwira (Archiwa, Biblioteki i Muzea Kościelne, 2017)
There is a wealth of information about the existence of libraries in antiquity. Historical sources indicate that already in the 6th century BC two Greek tyrants: Peisistratos of Athens and Polycrates of Samos had small collections. There had to be favourable conditions which allowed for establishing libraries. At the turn of the 4th century BC, sophists came to Athens and prepared citizens for public life. Then a new political structure was formed-democracy, which required education and knowledge from Athenians. There was the increased demand for such a model of education that would shape a human-citizen. At that time in Athens, numerous philosophical and rhetorical schools were founded. The creation of book collections was influenced by various factors. One of the book lovers was Plato, who founded his own school of philosophy, the Academy in Athens around 387 BC. We know that Plato collected and systematically enlarged his book collection, but it seems that his library was not too extensive. Aristotle of Stagira, the creator of the Athenian philosophical school, is considered to have been the first book collector. He held his collection in Lyceum, which was acquired by him around 335 BC.